Handbook of economic growth. - Aghion, Philippe; Durlauf, Steven N. (Handbooks in economics, 2005)
The Handbooks in Economics series continues to provide the various branches of economics with handbooks which are definitive reference sources, suitable for use by professional researchers, advanced graduate students, or by those seeking a teaching supplement. The Handbook of Economic Growth, edited by Philippe Aghion and Steven Durlauf, with an introduction by Robert Solow, features in-depth, authoritative survey articles by the leading economists working on growth theory.